2017
DOI: 10.1080/23262133.2017.1300037
|View full text |Cite
|
Sign up to set email alerts
|

Building a central nervous system: The neural stem cell lineage revealed

Abstract: Neural stem cells (NSCs) are a multipotent, self-renewing source of undifferentiated cells in the periventricular region of the mammalian central nervous system (CNS). Since their original discovery 25 years ago, much has been learned about their development, persistence, localization, properties and potential. Herein we discuss the current state of knowledge pertaining to neural stem cells with a focus on the lineage relationship between two NSC populations along the neuraxis and their regionally distinct nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…The spatial pattern of cell division correlates well with the transition from stem to differentiation state, which is displayed from the neurosphere’s core to its external domains (Fig. 4 , and 5 ). Further support for this conclusion came by staining for phH3 and Sox2 (Fig.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The spatial pattern of cell division correlates well with the transition from stem to differentiation state, which is displayed from the neurosphere’s core to its external domains (Fig. 4 , and 5 ). Further support for this conclusion came by staining for phH3 and Sox2 (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…In the adult, however, the generation of new neurons is extremely limited. Yet, many studies have confirmed the existence of few NSC reservoirs in the dentate gyrus of the hippocampus, subventricular zone (SVZ) in the walls of the lateral ventricles, as well as in other regions, that can undergo neurogenesis throughout life upon specific conditions 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Also of particular importance to regenerative medicine is the lineage from which the different types of nerves and glial cells are derived. The multipotent stem cell which can differentiate into any CNS cell is called neural stem cell (NSC) . Differentiation of nerve progenitor cells results in 3 structurally different categories of nerves only differing in the number of dendrites they possess .…”
Section: Cells and Scaffolds For Brain Tissue Engineeringmentioning
confidence: 99%
“…Also, attenuation of the foreign‐body reaction to any biomaterial/microelectrodes may require systemic or local delivery of anti‐inflammatory agents. In addition, unintended functionality will also need to be evaluated to avoid aberrant connectivity and thus achieve desired functional restoration …”
Section: Cells and Scaffolds For Brain Tissue Engineeringmentioning
confidence: 99%
“…In 1992, NSCs were first isolated from the adult striatal tissue, including the subventricular zone and adult mice brain tissue (Reynolds and Weiss 1992 ). Following the discovery of NSCs, significant advances have been made in our understanding about its localization, development, persistence, properties, and potential in the central nervous system (Xu et al 2017 ). Multipotent NSCs can be isolated and cultured from primary cortical or hippocampal cultures after passage in the presence of mitogenic growth factors (Gage et al 1995 ), such as epidermal growth factor and basic fibroblast growth factor (bFGF).…”
Section: Introductionmentioning
confidence: 99%